Molnupiravir treatment of 18 cats with feline infectious peritonitis: A case series - Okihiro Sase (Journal of Veterinary Internal Medicine, 2023)
Abstract Background Feline infectious peritonitis (FIP) is a viral disease in cats, caused by certain strains of coronavirus and has a high case fatality rate. Objective This case series reports the outcomes of treatment of cats with FIP using molnupiravir. Animals Eighteen cats diagnosed with FIP at the You‐Me Animal Clinic, Sakura‐shi, Japan between January and August 2022, and whose owners gave informed consent to this experimental treatment. Methods For this prospective observational study, molnupiravir tablets were compounded in‐house at the You‐Me Animal Clinic. Owners administered 10‐20 mg/kg PO twice daily. Standard treatment duration was 84 days. Results Among 18 cats, 13 cats had effusive FIP and 5 had noneffusive FIP. Three cats had neurological or ocular signs of FIP before treatment. Four cats, all with effusive FIP, died or were euthanized within 7 days of starting treatment. The remaining 14 cats completed treatment and remained in remission at the time of writing (139‐206 days after starting treatment). Elevated serum alanine transaminase (ALT) activity was found in 3 cats, all at Days 7‐9, and all recovered without management. Two cats with jaundice were hospitalized, 1 during treatment (Day 37) and 1 with severe anemia at the start of treatment. Conclusions and Clinical Importance This case series suggests that molnupiravir might be an effective and safe treatment for domestic cats with FIP at a dose of 10‐20 mg/kg twice daily.